Determination of DNA quality extracted from food products / Syarifah Faezah Syed Mohamad, Nur Amirah Abdul Hamid and Muhammad Syazwan Yassin Md Som - Syed Mohamad, Syarifah Faezah; Abdul Hamid, Nur Amirah; Md Som, Muhammad Syazwan Yassin (Universiti Teknologi MARA Cawangan Pahang, 2020)
Deoxyribonucleic acid or DNA is the hereditary molecule of living things. Food products mostly contain ingredients originated from animals and plants. Food adulteration is the main concern in food industry. Food manufacturers might substitute raw materials with other cheap and abundant materials which is species substitution. With the help of DNA, scientists are able to identify the species used in the food products. The objective of this study are to determine the presence of DNA isolated from selected food products and to access the quality of the extracted DNA using gel electrophoresis. DNA were extracted using DNeasy™ Blood and Tissue kit (Qiagen, Germany) following manufacturer protocols with slight modifications. The extracted DNA's quality was then subsequently evaluated on 1.5% agarose gel. The food products chosen were chicken sausages, meat patty and chocolate confectioneries. Results obtained showed positive DNA bands in sausages and meat patty, but no bands were observed from chocolate confectioneries. Extracting DNA from a complex and highly processed foods was a very challenging task. Thus, it requires optimization and improvisation of the extraction procedures in order to achieve high quality DNA bands